2016
DOI: 10.1038/srep22138
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the genome-wide DNA methylation pattern of porcine ovaries using reduced representation bisulfite sequencing

Abstract: Substantial evidence has shown that DNA methylation regulates the initiation of ovarian and sexual maturation. Here, we investigated the genome-wide profile of DNA methylation in porcine ovaries at single-base resolution using reduced representation bisulfite sequencing. The biological variation was minimal among the three ovarian replicates. We found hypermethylation frequently occurred in regions with low gene abundance, while hypomethylation in regions with high gene abundance. The DNA methylation around tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 60 publications
12
31
0
Order By: Relevance
“…Non-CpG information was also obtained in the present study, CAG was the most common sequence motif in the CHG mC sites, as also found in other studies [ 26 ], and the sequence motif in CHH differed between the two groups. The methylation levels near the TSS were the lowest of all the gene functional regions, which was consistent with the results found in pig ovaries by RRBS [ 27 ]. Most hypermethylation CGI (over 68%) were located in distal intergenic regions, while only 1.5% were in UTR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Non-CpG information was also obtained in the present study, CAG was the most common sequence motif in the CHG mC sites, as also found in other studies [ 26 ], and the sequence motif in CHH differed between the two groups. The methylation levels near the TSS were the lowest of all the gene functional regions, which was consistent with the results found in pig ovaries by RRBS [ 27 ]. Most hypermethylation CGI (over 68%) were located in distal intergenic regions, while only 1.5% were in UTR.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence has revealed that ovarian maturation is regulated by DNA methylation [ 5 , 6 ]. By profiling the methylome of porcine ovaries, researchers examined the methylation changes during the process of sexual and ovarian maturation in pigs [ 7 ]. Similar studies also found that DNA methylation alterations influenced gene expression profiles in the goat hypothalamus during the onset of puberty [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the DMRs (CP vs DP) suffered more hypomethylation (391/775 DMRs) than hypermethylation (384/ 775 DMRs) in the ear, suggested the DNA methylation status in the DMRs altered and phenotype changed in cloned pig, this was consistent with the DNA methylation context of skeletal muscle in abnormal and normal cloned pig . Therefore, the methylation context of the ear and blood were different, which was consistent with the results of the DNA methylation in the ovary and intestine of pigs (Yuan et al, 2016). Furthermore, the average sequencing depth was more than 25X, the methylation conversion of reads with a coverage of >10X were more than 87.82% and >74.93% of bases were aligned to the reference genome.…”
Section: Phenotype and Methylation Were Differentsupporting
confidence: 81%
“…DNA methylation is an epigenetic mechanism that regulates gene expression in response to environmental stimuli (39,41). Although the genome-wide DNA methylation patterns of many tissues have been reported (42)(43)(44), the methylation maps in CL remain largely undetermined. In this study, we systematically investigated the global methylation patterns of CLs in sows.…”
Section: Discussionmentioning
confidence: 99%